2009
DOI: 10.1177/1470320309102314
|View full text |Cite
|
Sign up to set email alerts
|

Association of the insertion/deletion polymorphism of the angiotensin-converting enzyme gene with type 2 diabetes in two ethnic groups of Jerba Island in Tunisia

Abstract: Introduction. The aim of the current study was to evaluate the role of angiotensin-converting enzyme (ACE) insertion/deletion (I/D) polymorphism on the prediction of type 2 diabetes in two ethnic populations from Jerba Island, Tunisia. Methods. In this study, we analysed the genotypic and the allelic distributions of the ACE I/D polymorphism and conducted a case/control association study between healthy normoglycaemic controls and diabetic patients in the two studied groups. ACE gene polymorphism was analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 32 publications
(38 reference statements)
4
23
0
Order By: Relevance
“…In this study, there was no statistically significant association between ACE genotypes with HD in T2DM patients and this is similar to other studies such as in Tunisia [20], but is dissimilar to other studies conducted in Tunisia [10], Egypt [16] and Iraqi [13], which found an increase inT2DM risk in D/D genotype individuals.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In this study, there was no statistically significant association between ACE genotypes with HD in T2DM patients and this is similar to other studies such as in Tunisia [20], but is dissimilar to other studies conducted in Tunisia [10], Egypt [16] and Iraqi [13], which found an increase inT2DM risk in D/D genotype individuals.…”
Section: Discussionsupporting
confidence: 56%
“…Although the polymorphism is located in a non-coding region, the D allele is associated with increased activity of ACE in serum [9]. There are highly inconsistent findings within all the major ethnic groups when the association of I/D polymorphism of ACE gene is studied with cardiovascular and renal complications and the risk for Type 2 Diabetes Mellitus (T2DM), where some studies have explained that the D allele is most frequent in T2DM and the associated complications in Tunisia [10] while others have found no association between ACE alleles frequencies with T2DM or cardiovascular disease (CVD) and renal disease in Malaysia and Indonesians [11]. The differences in the findings are largely due to the multifactorial or polygenic nature of these disorders, as evidenced by the variations of disease outcomes modulated by the between the gene to gene or gene to environment interactions [6].…”
Section: Introductionmentioning
confidence: 99%
“…1, compared with ACE I allele, presence of D allele conferred a significant risk for T2D (OR=1.33; 95% CI, 1.10-1.61; p=0.003). Except for three studies suggesting the protective effect of D allele [10,13,14] and one with the neutral effect [11], others consistently favored the risk effect, especially for the more recently studies [12,25]. In addition, under the additive model, this trend was potentiated after comparing homozygotes of D allele with I allele (DD versus II) with a 90% increased risk (95% CI, 1.30-2.78; p=0.0008).…”
Section: Main Meta Resultsmentioning
confidence: 99%
“…They also found that DD genotype is involved in the pathogenesisof T2DM in Jerbian population. Moreover, Baroudiet al, (2009) also emphasized on the vital role of ethnicity, which should be considered an important factor in this genetic studies of T2DM [22]. In a cohort study of In this study, a nonsignificant association between the allelic frequencies and the presence of neuropathy,retinopathy and cardiac events in patients with and without nephropathy were found.…”
Section: Levels Of Beta-2 -Microglobulin In Diabetic Nephropathic Patmentioning
confidence: 47%